2014
DOI: 10.1016/j.cognition.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Lying relies on the truth

Abstract: Cognitive models of deception focus on the conflict-inducing nature of the truth activation during lying. Here we tested the counterintuitive hypothesis that the truth can also serve a functional role in the act of lying. More specifically, we examined whether the construction of a lie can involve a two-step process, where the first step entails activating the truth, based upon which a lie response can be formulated in a second step. To investigate this hypothesis, we tried to capture the covert truth activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 45 publications
5
55
0
1
Order By: Relevance
“…Evidence has been found for the notion that the truth response is activated first, thereby inducing response conflict and an increased need for response inhibition to prevent the truth from slipping out (Debey, Ridderinkhof, De Houwer, & Verschuere, submitted for publication;Duran, Dale, & McNamara, 2010;Hadar, Makris, & Yarrow, 2012;Vartanian et al, 2013). However, the truth may initially also be kept active in working memory to help the formulation of an alternative, deceptive response (Ambach, Stark, & Vaitl, 2011;Debey, De Houwer, & Verschuere, 2014;Visu-Petra, Miclea, & Visu-Petra, 2012). Finally, shifting may help to flexibly shift between the mental sets associated with truthful and deceptive responses (Visu-Petra, Varga, Miclea, & Visu-Petra, 2013;Visu-Petra et al, 2012).…”
Section: Executive Control and Lyingmentioning
confidence: 93%
“…Evidence has been found for the notion that the truth response is activated first, thereby inducing response conflict and an increased need for response inhibition to prevent the truth from slipping out (Debey, Ridderinkhof, De Houwer, & Verschuere, submitted for publication;Duran, Dale, & McNamara, 2010;Hadar, Makris, & Yarrow, 2012;Vartanian et al, 2013). However, the truth may initially also be kept active in working memory to help the formulation of an alternative, deceptive response (Ambach, Stark, & Vaitl, 2011;Debey, De Houwer, & Verschuere, 2014;Visu-Petra, Miclea, & Visu-Petra, 2012). Finally, shifting may help to flexibly shift between the mental sets associated with truthful and deceptive responses (Visu-Petra, Varga, Miclea, & Visu-Petra, 2013;Visu-Petra et al, 2012).…”
Section: Executive Control and Lyingmentioning
confidence: 93%
“…During the generation of a false response, the cognitive system does not simply elaborate a statement, but it carries out several executive tasks: it inhibits the true statement and, subsequently, it produces a false statement [9]. Moreover, the generation of a lie requires to monitor the reaction of the interlocutor and to adjust the behavior congruently to the lie [10].…”
Section: Introductionmentioning
confidence: 99%
“…This result showed that participants could keep more information in the WM when they gave honest response than when they deceived in high-load tasks. Previous studies revealed that participants needed to make up lies based on the truth-related information in the WM when they tried to lie[7,8], so that this construction process consumed the WM resources. Considering the limitation of the WM capacity, we assumed that the WM was insufficient for both the information maintenance and lie construction during the deception in the high-load tasks.…”
Section: Discussionmentioning
confidence: 99%
“…And this judgment is made based on the truth-related information retrieved from memory [47]. If the decision is to deceive, individuals should construct lies based on the truth-related information before they respond [8]. Whereas, if individuals decide to tell the truth, they do not need this construction process, and can give the truthful responses.…”
Section: Introductionmentioning
confidence: 99%